Do Universities Improve Local Economic Resilience? - Greg Howard; Russell Weinstein; Yuhao Yang (Institute of Labor Economics (IZA), 2021)
We use a novel identification strategy to investigate whether regional universities make their local economies more resilient to adverse economic shocks. Our strategy is based on state governments assigning normal schools (to train teachers) and insane asylums to counties between 1830 and 1930. Normal schools later became much larger regional universities while asylum properties mostly continue as small state-owned psychiatric health facilities. Because site selection criteria were similar for these two types of institutions, comparing counties assigned a normal school versus an insane asylum identifies the effect of a regional university. We find that having a regional university roughly offset the negative effects of exposure to manufacturing declines, and we attribute a significant share of this resilience to the resilience of regional public university spending.
Keywords: R10; I23; J20; 330; manufacturing decline; universities and economic growth; resilience